Influence of increased vitamin levels for the first 35 d postweaning on breeding and subsequent lactation performance of sows - Lynch, G.; Tokach, Michael D.; Nelssen, Jim L.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Four hundred and eight sows were used to evaluate the effects of feeding high levels of vitamins (2 to 7 times average inclusion rate) for the first 35 d postbreeding on later reproduction performance. number of pigs born alive and number born dead following feeding high vitamin levels showed a numeric advantage compared with sows fed the control diet. These numeric responses resulted in trends toward higher number weaned (9.75 vs 9.54) and litter weaning weight (l 07.8 vs 105.4 lb). Further research needs to be conducted to determine which vitamin or vitamins may have an influence on embryo survival.
Keywords: Swine; Sows; Gestation; Reproduction; Vitamins